Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Handphone Pada Toko Surya Phone di Samarinda (Studi Kasus Pada Toko Surya Phone 6 Jl. KH. Abul Hasan) - Sunarto 3, Violin1, Robin jonathan 2 (EKONOMIA, 2021)
The Influence of the Marketing Mix on Purchasing Handphone Decisions at Surya Phone store Samarinda (a case study on Surya Phone 6 store at Jl. KH. Abul Hasan). Under the guidance of Mr. Robin Jonathan as a 1st mentor and Mr. Sunarto as the 2nd Mentor.The purpose of this study is: 1.) to find out the effect of the Product on purchasing decisions at Surya Phone store Samarinda. 2.) To find out the effect of Price on purchasing decisions at Surya Phone store Samarinda 3.) To find out the effect of Location on purchasing decisions at Surya Phone store Samarinda. 4.) To find out the effect of Promotion on purchasing decisions at Surya Phone store Samarinda. 5.) To find out the effect of product, price, location, and promotion together with the purchasing decision at Surya Phone store Samarinda.This study was done at Surya Phone 6 store on KH. Abul HasanÂ Street Samarinda. The sample used in this study were 100 respondents with a Non Probability Sampling Method and the technique sampling is Non Random Sampling. Data was collected by distributing questionnaires and using likert scale for each indicator. The Analytical tool used is Multiple Linear Regression at SPSS V25 Programm. The results of this study shows : 1.) Product variable did not significantly influence of purchasing decisions at Surya Phone store Samarinda. 2.) Price variable did not significantly influence of purchasing decisions at Surya Phone store Samarinda. 3.) Place variable did significantly influence of purchasing decisions at Surya Phone store Samarinda. 4.) promotion variable did significantly influence of purchasing decisions at Surya Phone store Samarinda. 5.) The variables of product, price, location, and promotion together significant effect on purchasing decisions at Surya Phone store Samarinda.